NK cells require immune checkpoint receptor LILRB4/gp49B to control neurotropic Zika virus infections in mice - Ha-Na Lee; Mohanraj Manangeeswaran; Aaron P. Lewkowicz; Kaliroi Engel; Monica Chowdhury; Mamatha Garige; Michael A. Eckhaus; Carole Sourbier; Derek D.C. Ireland; Daniela Verthelyi (JCI Insight, 2022)
Immune cells express an array of inhibitory checkpoint receptors that are upregulated upon activation and limit tissue damage associated with excessive response to pathogens or allergens. Mouse leukocyte immunoglobulin like receptor B4 (LILRB4), also known as glycoprotein 49B (gp49B), is an inhibitory checkpoint receptor constitutively expressed in myeloid cells and upregulated in B cells, T cells, and NK cells upon activation. Here, we report that expression of LILRB4, which binds Zika virus (ZIKV), was increased in microglia and myeloid cells infiltrating the brains of neonatal mice with ZIKV-associated meningoencephalitis. Importantly, while C57BL/6 mice developed transient neurological symptoms but survived infection, mice lacking LILRB4/gp49B (LILRB4 KO) exhibited more severe signs of neurological disease and succumbed to disease. Their brains showed increased cellular infiltration but reduced control of viral burden. The reduced viral clearance was associated with altered NK cell function in the absence of LILRB4/gp49B. In naive animals, this manifested as reduced granzyme B responses to stimulation, but in ZIKV-infected animals, NK cells showed phenotypic changes that suggested altered maturation, diminished glucose consumption, reduced IFN-γ and granzyme B production, and impaired cytotoxicity. Together, our data reveal LILRB4/gp49B as an important regulator of NK cell function during viral infections.